DETERMINANTS OF POSTNATAL DEPRESSION IN RURAL GHANA: FINDINGS FROM THE DON POPULATION BASED COHORT STUDY. Issue 2 (25th November 2013) - Weobong, Benedict; ten Asbroek, Augustinus HA; Soremekun, Seyi; Danso, Samuel; Owusu‐Agyei, Seth; Prince, Martin; Kirkwood, Betty R.
<x xml:space="preserve">Abstract</x> Background Risk factors for postnatal depression (PND), one of the most pervasive complications of child bearing, are poorly understood in Africa. A recent systematic review of 31 studies found that the strongest predictors are social and economic disadvantage and gender‐based factors; only six of these studies were community based, and almost all were in South Asia. Methods Cohort study nested within 4 weekly surveillance of all women of reproductive age to identify pregnancies and collect data on births and deaths in the Kintampo Health Research Centre study area of Ghana. Women were screened for depression during pregnancy and after birth using the Patient Health Questionnaire to ascertain DSM‐IV major or minor depression. Information was collected on determinants relating to the mother, birth, and baby, which were examined using logistic regression; effect sizes reported as relative risks with 95% confidence intervals. Results Thirteen thousand nine hundred and twenty nine women were screened both during pregnancy and after birth, of whom 13, 360 (95.9%) had complete data on potential determinants. Two hundred and fifty five (3.8%, 95% CI: 3.5%, 4.1%) had PND. Antenatal depression (AND) was the strongest determinant accounting for 34.4% of PND cases. Other determinants were season of delivery, peripartum/postpartum complications, newborn ill health, still birth, or neonatal death. Common determinants were observed for onset and persistent depression. Conclusions Although most AND resolves in this setting, more than a third of women with PND also had AND. Adverse birth‐ and baby‐related outcomes are the other main determinants. We recommend that programs detect and treat depression during pregnancy and provide support to women with adverse birth outcomes.